APPLICATION OF VARIOUS CONCENTRATIONS OF LIQUID ORGANIC FERTILIZER FROM COFFEE FRUIT SKIN WASTE ON THE GROWTH OF ARABICA COFFEE SEEDLINGS (Coffea arabica L.) - Junardi, Flavianus; Ariefin, Muhammad Noor; Taopan, Rizki Adiputra (Fruitset Sains : Jurnal Pertanian Agroteknologi, 2024)
The excessive and continuous use of inorganic fertilizers can indirectly reduce soil quality and fertility. This can result in high production costs, yet unsatisfactory yields and product quality. One effort to address this issue is by using organic liquid fertilizer derived from coffee pulp waste. This study aims to determine the effects and the appropriate dosage of liquid organic fertilizer made from coffee pulp waste on the growth of Arabica coffee seedlings. The research was conducted at the Wulang Pari Coffee Processing Unit in Laci Carep Village, Langke Rembong Subdistrict, Manggarai Regency, East Nusa Tenggara, from July 2024 to August 2024. The study utilized a Randomized Block Design with one factor, which was the concentration of liquid organic fertilizer from coffee pulp waste consisting of 5 treatment levels and repeated 4 times. Each treatment consisted of 5 plants, resulting in a total of 100 plants. From each experimental unit, 3 sample plants were taken, resulting in 75 sample plants. The treatment levels used were K0 = Control (0 ml/application), K1 = 20 ml/application, K2 = 40 ml/application, K3 = 60 ml/application, and K4 = 80 ml/application. The results of the study concluded that the application of various concentrations of liquid organic fertilizer from coffee pulp waste did not significantly differ in their effects, and the concentration P4 (80 ml/application) provided the optimal dosage for research parameters such as plant height, number of leaves, and number of shoots.